Workers' compensation claims for musculoskeletal disorders and injuries of the upper extremity and knee among union carpenters in Washington State, 1989–2008. Issue 4 (24th February 2015) - Lipscomb, Hester J.; Schoenfisch, Ashley L.; Cameron, Wilfrid; Kucera, Kristen L.; Adams, Darrin; Silverstein, Barbara A.
Abstract: Background: Numerous aspects of construction place workers at risk of musculoskeletal disorders and injuries (MSDIs). Work organization and the nature of MSDIs create surveillance challenges. Methods: By linking union records with workers' compensation claims, we examined 20‐year patterns of MSDIs involving the upper extremity (UE) and the knee among a large carpenter cohort. Results: MSDIs were common and accounted for a disproportionate share of paid lost work time (PLT) claims; UE MSDIs were three times more common than those of the knee. Rates declined markedly over time and were most pronounced for MSDIs of the knee with PLT. Patterns of risk varied by extremity, as well as by age, gender, union tenure, and predominant work. Carpenters in drywall installation accounted for the greatest public health burden. Conclusions: A combination of factors likely account for the patterns observed over time and across worker characteristics. Drywall installers are an intervention priority. Am. J. Ind. Med. 58:428–436, 2015. © 2015 Wiley Periodicals, Inc.